Associations between Migrant status and sexually transmitted infections among female sex workers in Tijuana, Mexico - Ojeda, Victoria D. (2009)
OBJECTIVE: To examine associations between migration and sexually transmitted infection (STI) prevalence among Mexican female sex workers (FSW). METHODS: FSW aged ≥18 years in Tijuana, Baja California (BC) underwent interviews and testing for HIV, syphilis, gonorrhea and Chlamydia. Multivariate logistic regressions identified correlates of STI. RESULTS: Of 471 FSW, 79% were migrants to BC. Among migrant FSW, prevalence of HIV, syphilis, gonorrhea, Chlamydia, and any STI was 6.6%, 13.2%, 7.8%, 16.3%, and 31.1% vs. 10.9%, 18.2%, 13.0%, 19.0%, and 42.4% among FSW born in BC. A greater proportion of migrant FSW were registered with local health services and were ever tested for HIV. Migrant status was protective for any STI in unadjusted models (Unadj. OR: 0.61, 95%CI: 0.39, 0.97). In multivariate models controlling for confounders, migrant status was not associated with an elevated odds of STI acquisition and trended towards a protective association. CONCLUSIONS: Unexpectedly, migrant status (vs. native-born status) appeared protective for any STI acquisition. It is unclear which social or economic conditions may protect against STI and whether these erode over time in migrants. Additional research is needed to inform our understanding of whether or how geography, variations in health capital, or social network composition and information sharing attributes can contribute to health protective behaviors in migrant FSW. By capitalizing on such mechanisms, efforts to preserve protective health behaviors in migrant FSW will help control STI in the population and may lead to the identification of strategies that are generalizable to other FSW.